The Sociohistorical Construction of the Identity of the Profession of Guidance Counsellors in Quebec from the Perspective of Interactions Between Its Regulatory Professional Body and Stakeholders - Cournoyer, Louis; Turcotte, Michel (Canadian Journal of Counselling and Psychotherapy, 2016)
Since its inclusion in the Quebec professional system, how has the identity of the profession of guidance counsellors been shaped through its regulatory professional body? Based on an interactionist perspective of the sociology of professions (Dubar, 2000), this article examines the notion of “the identity of a profession” as a sociohistorical construct. An analysis of the content of the annual reports of the Ordre des conseillers et conseillères d’orientationdu Québec regulatory professional body of guidance/career counsellors in Quebec) from 1973 to 2012 identifies the types of interactions between the regulatory professional body and stakeholders in its political, economic, institutional, and other environments. The results suggest that the Ordre participates in three types of identity transactions based on the stakeholders involved: (a) partnership, interdependent, and knowledge transfer relationships; (b) cooperative activities on a case-by-case and ongoing monitoring basis to pursue common conditions for positioning, development, and socioprofessional outreach; and (c) positive promotion of the profession through service exchange.